Firefox hacks : tips & tools for next-generation web browsing - McFarlane, Nigel (O'Reilly Media, 2005)
"Firefox Hacks explains how to customize Firefox's deployment, appearance, features, and functionality - delivering techniques, tools, and strategies for making the most out of Firefox's outstanding flexibility." "Whether you're a crusty hacker, a bored web surfer, a contemporary web designer, or a frustrated IT professional, you'll find all the user-friendly tips, tools, and tricks you need to make a productive switch to Firefox."--Jacket